You're a rude pig, Bertie! - Boldt, Claudia (Northsouth, 2013)
Bertie is the most vain, rude and outspoken pig you'll ever meet. He can't help offending his friends and pretty soon he doesn't have any left. But a beautiful bunny and a disastrous party all lead Bertie to a startling realization, and a change of heart